2021
DOI: 10.1111/jce.15051
|View full text |Cite
|
Sign up to set email alerts
|

Ablation outcomes for atypical atrial flutter versus recurrent atrial fibrillation following index pulmonary vein isolation

Abstract: Background Data related to electrophysiologic characteristics of atypical atrial flutter (AFL) following atrial fibrillation (AF) ablation and its prognostic value on repeat ablation success are limited. Methods We studied consecutive patients who underwent a repeat left atrial (LA) ablation procedure for either recurrent AF or atypical AFL, at least 3 months after index AF ablation, between January 2012 and July 2019. The demographics, clinical history, procedural data, complications, and 1‐year arrhythmia‐fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 17 publications
1
4
1
Order By: Relevance
“…AAFl has reoccurred in 12.7% of patients. It has been found that left atrial diameter and volume were greater in patients with the recurrence of AAFl than in patients who developed AF after prior ablation of the atrium [10]. We did not analyze this variable, but interestingly, contrary to our findings, male sex or antiarrhythmics prescription was not associated with arrhythmia-free survival in this analysis.…”
Section: Discussioncontrasting
confidence: 93%
“…AAFl has reoccurred in 12.7% of patients. It has been found that left atrial diameter and volume were greater in patients with the recurrence of AAFl than in patients who developed AF after prior ablation of the atrium [10]. We did not analyze this variable, but interestingly, contrary to our findings, male sex or antiarrhythmics prescription was not associated with arrhythmia-free survival in this analysis.…”
Section: Discussioncontrasting
confidence: 93%
“…Clinically, atypical flutters sustained by AR drivers can be common after PVI, affecting up to 10% of patients following radiofrequency ablation. 44 , 45 , 46 , 47 Thus, our study provides reasonable explanation for the incidence of these tachyarrhythmias via anatomically AR around the mitral valve. The remaining 90% of recurrent AF cases may be attributed to emergent or preserved FRs, as previously suggested.…”
Section: Discussionsupporting
confidence: 64%
“…To our knowledge, this is the first study reporting follow‐up of MAF ablation out to 4 years. The recurrence of atrial arrhythmias after ablation remains high and seems to increase over time 5,6,22,25,26 . In this study, the MIL line was associated with greater freedom from recurrent atrial arrhythmias over a 4‐year follow‐up period, with less recurrent atrial flutter.…”
Section: Discussionmentioning
confidence: 57%